Mapping the Specific Pathways to Early-Onset Mental Health Disorders: The “Watch Me Grow for REAL” Study Protocol - Doyle, Frances L.; Mendoza Diaz, Antonio; Eapen, Valsamma; Frick, Paul J.; Kimonis, Eva R.; Hawes, David J.; Moul, Caroline; Richmond, Jenny L.; Mehta, Divya; Sareen, Sinia; Morgan, Bronte G.; Dadds, Mark R. (Frontiers in Psychiatry, 2020)
Background: From birth, the human propensity to selectively attend and respond to critical super-stimuli forms the basis of future socio-emotional development and health. In particular, the first super-stimuli to preferentially engage and elicit responses in the healthy newborn are the physical touch, voice and face/eyes of caregivers. From this grows selective attention and responsiveness to emotional expression, scaffolding the development of empathy, social cognition, and other higher human capacities. In this paper, the protocol for a longitudinal, prospective birth-cohort study is presented. The major aim of this study is to map the emergence of individual differences and disturbances in the system of social-Responsiveness, Emotional Attention, and Learning (REAL) through the first three years of life to predict the specific emergence of the major childhood mental health problems, as well as social adjustment and impairment more generally. A further aim of this study is to examine how the REAL variables interact with the quality of environment/caregiver interactions. Methods/Design: A prospective, longitudinal birth-cohort study will be conducted. Data will be collected from four assessments and mothers’ electronic medical records. Discussion: This study will be the first to test a clear developmental map of both the unique and specific causes of childhood psychopathology and will identify more precise early intervention targets for children with complex comorbid conditions.